DECONSTRUCTING CRITICAL THINKING SKILLS PROVISION: THE NORMATIVE AND THE TRANSFORMATIVE (BALEAP Journal of Research and Practice, 2025)
Critical thinking skills are at the core of Higher Education and EAP practice; however, there is little consensus in defining the term and its elusive nature. We approached this landscape from a social-constructivist perspective aiming at deconstructing views and practices as well as generating ideas and alternative avenues for research and practice. We conducted a small-scale survey on how EAP practitioners view the relevant provision at their institutions, how they think teaching critical thinking skills can be more focused and effective, and how they view their role in this transition. We used this data as a springboard for our workshop at BALEAP 2023 Conference to initiate a cycle of de- and re-construction of EAP practice. This reflective report adopts Kolb’s cycle of reflective practice to analyse the outcomes of this process. Our results indicate that the emerging themes link under two larger concepts: instructional approaches and acknowledging cultural diversity. We identified a positive move towards more holistic, post-method instructional approaches to meet learners’ needs without losing sight of active student engagement. The results also highlight that diverse views and perceptions of CT skills due to cultural and educational differences were acknowledged and deficit models and/or stereotyping were rejected and identified as main challenges EAP tutors face in their practice.